The Effect of Budget Targets Clarity, Accounting Control, and Reporting System on Performance Accountability in the Transportation Service Of Central Java Province (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the effect of clarity of budget targets, accounting control, and reporting systems on performance accountability at the Central Java Provincial Transportation Agency. The population in this study were all employees of the Central Java Provincial Transportation Agency, conducted by sampling, with a census sample (Finance Division), a sample of 30 respondents was obtained. The analysis technique used was multiple linear regression by distributing questionnaires (google form) to respondents. Scoring of respondents' answers to questions used a Likert scale. The results of the study can be concluded that: 1.) Clarity of budget targets does not affect performance accountability. 2.) Accounting control does not affect performance accountability. 3.) The reporting system has a positive and significant effect on performance accountability.